Development and characterization of shelf stable quick cooking carrot - Yadav, Y. S. (2018)
Carrot (Daucus carota L.) being a rich source of bioactive and functional components helps significantly as an important health-promoting biomaterial. Presevance of functional components with extended shelf life and ease in use are the common challenges associated with the vegetables of perishable catagories. To meet the objectives of developing shelf stable quick cooking carrot, effect of blanching, freezing and salt treatments were assessed for the dehydrated and rehydrated products characteristics over the control. Pretreated carrot cubes were subjected to hot air drying at 70°C in order to get shelf stable carrot. Depending on the rehydrated product characteristics, treatment conditions were screened out and were characterized on various aspects such as dehydration, rehydration, gravimetric and optical characteristics, proximate composition, β-carotene, total antioxidant capacity, total phenol content. Results were statistically evaluated using two-way ANOVA to elucidate the effects of treatment provided to carrot cubes. Significant effects of treatments were observed for physicochemical, dehydration, rehydration and optical characteristics.